Theoretical studies on the intramolecular cyclization of 2,4,6-t-Bu3C6H2P=C: and effects of conjugation between the P=C and aromatic moieties - Yoshifuji, Masaaki; Ito, Shigekazu (Beilstein Journal of Organic Chemistry, 2014)
The intramolecular C–H insertion of the Mes*-substituted phosphanylidenecarbene [Mes*P=C:] (Mes* = 2,4,6-t-Bu3C6H2) and physicochemical properties of the cyclized product, 6,8-di-tert-butyl-3,4-dihydro-4,4-dimethyl-1-phosphanaphthalene were studied based on ab initio calculations. Whereas the alternative Fritsch–Buttenberg–Wiechell-type rearrangement requires almost no activation energy, the intramolecular cyclization needs an activation energy of 12.3 kcal/mol at the MP2(full)/6-31G(d) condition. DFT calculations supported that the optimized structure of the cyclization product of Mes*P=C: suggests remarkable conjugation effects between the nearly coplanar P=C skeleton and the aryl moiety.
Keywords: 3,4-dihydro-1-phosphanaphthalene; intramolecular cyclization; organophosphorus; phosphanylidenecarbene; steric protection; theoretical calculation